Fragmentation and Memory : Meditations onyChristian Doctrine. - Schehr, Lawrence R. (Fordham University Press, 2009)
This title focuses on the way a number of French literary narratives written in the realist tradition show a dynamic balance between the desire of the author/narrator to present a verisimilar world and the need for aesthetic balance. While the works studied range from 1835 to 1938, they share a perspective on the relations between and the need to engage questions of realist verisimilitude and narrative interest and aesthetics.